The Ethical Perspective of Millennial Accountants in Responding to Opportunities and Challenges of Blockchain 4.0 - Sendy Dwi Haryanto; Erina Sudaryati (Journal of Accounting and Investment, 2020)
Research aims: This study aims to provide a perspective on the professional ethics of a millennial accountant in applying blockchain technology to improve his professionalism, and discusses the issue of blockchain ethical challenges for an accountant's profession